A scoping review of interaction dynamics in minimally verbal autistic individuals - Boorom, Olivia; Liu, Talia (Frontiers in Psychology, 2024)
Interaction dynamics provide information about how social interactions unfold over time and have implications for communication development. Characterizing social interaction in autistic people who are minimally verbal (MV) has the potential to illuminate mechanisms of change in communication development and intervention. The purpose of this scoping review was to investigate the current evidence characterizing interaction dynamics in MV autistic individuals, methods used to measure interaction dynamics in this population, and opportunities for future research. Articles were included if participants were diagnosed with autism, considered MV, if interaction occurred with a human communication partner during live in-person interaction, and if variables were derived by measuring the relationship between behaviors in both partners. The seven articles included in this review demonstrate that limited research describes interaction dynamics in this population, and that behavioral coding measures can be leveraged to assess constructs such as turn-taking, social contingency, and balance in social interactions. While there is some evidence describing how MV autistic individuals and their communication partners construct reciprocal interaction, there is variability in how interaction dynamics are measured and limited evidence describing individual differences. Recommendations for future research are discussed.